ENGINEERING DESIGN OF A MANIPULATOR FOR MOUNTING AN AIR SUSPENSION COMPRESSOR TO A CAR CHASSIS - Miroslav BLATNICKÝ; Ján DIŽO; Dalibor BARTA; Iwona RYBICKA (Scientific Journal of Silesian University of Technology. Series Transport, 2020)
This article is aimed at the engineering design of a manipulator, which is pneumatically controlled. It will serve for mounting the compressor of an air suspension system to the chassis of a sport utility vehicle (SUV) produced in the Slovak Republic. The manipulator will be used on an assembly line, on which SUVs are assembled. The designed device belongs to a group of dedicated devices, which are not produced within a serial production, however, it is the only functional prototype. Together with the manipulator structure, a pneumatic part of the assembly line including individual components, schemes and the pneumatic system will be proposed. Within the project process, all necessary customer demands, technical and safety standards have to be met. Moreover, ergonomic requirements for handling the device and other acts on the workplace have to be considered.